Differentiation on sports lessons with ball games in 3rd and 4th grades (Training and Practice : Journal of Educational Sciences, 2018)
When determining the aims of physical education, the National Curriculum enhances the regular provision of physical activities, which plays an important role in the life of students also when growing up. It is important to socialize children by keeping lifelong active and healthy lifestyle in focus. As future teachers we regarded it to be crucial for children to experience the pleasure of movement with the help of ball games; therefore it is important for pedagogues to design variable playful lessons providing experiences matching the age characteristics of children. One of the basic pillars of education for healthy lifestyle is to participate in efficient sport lessons matching the level of training of students, which motivates them for continuous development. With the help of Polar OH1 pulse meters the stamina and resilience of children may be measured objectively.